2020
DOI: 10.1111/1440-1703.12093
|View full text |Cite
|
Sign up to set email alerts
|

The effect of species extinctions on island biogeographic patterns

Abstract: The study of island systems has provided the basis of much of what we understand about a number of biogeographic patterns. However, islands have also suffered numerous extinctions as a result of human activities. The extent to which these extinctions have influenced the many different patterns we study as island biogeographers, and thus what we consider to be “natural”, is largely unknown. Here, we use a simulation approach to illustrate the impacts of anthropogenic extinctions on various macroecological and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Half of these loses have been from islands. Globally, endemic species restricted to islands represent more than 60% of known terrestrial extinctions in the last 500 years (Matthews et al, 2020). Two of the extinctions (Labrador duck and Dawson caribou) were driven by over‐harvest and the remainder resulted from habitat loss or modifications for species that occurred in narrow ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of these loses have been from islands. Globally, endemic species restricted to islands represent more than 60% of known terrestrial extinctions in the last 500 years (Matthews et al, 2020). Two of the extinctions (Labrador duck and Dawson caribou) were driven by over‐harvest and the remainder resulted from habitat loss or modifications for species that occurred in narrow ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 938 extinct species and infraspecies (subspecies and varieties) on the IUCN Red List, 93.8% are nationally endemic (IUCN, 2022). While 61% of species listed on the IUCN Red List as extinct were confined to islands (Matthews et al, 2020), a large proportion of global extinctions are also driven by the loss of nationally endemic species from continental nations. For example, in Canada, over one‐third of the species (excluding populations and designatable units) assessed as extinct by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC) under the Species at Risk Act (2002) are nationally endemic (Government of Canada, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses indicate that CR species in particular are threatened by introduced species, highlighting the urgency required to deal with this issue on many islands before it is too late. While also an issue in continental systems, the effects of biological resource use, and especially hunting, are particularly acute on islands due to the small population sizes of many island endemics coupled with the small nature of the island themselves and thus lack of refugia (Matthews, Leidinger, & Cabral, 2020; Steadman, 2006; Whittaker & Fernández‐Palacios, 2007). While all the aforementioned drivers are detrimental when occurring in isolation, we found that many species are affected by more than one driver and it is likely that certain drivers will interact in a multiplicative fashion (Holdaway & Jacomb, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears likely that human agency, in the form of hunting and habitat disruption, along with other factors such as climate change, did play a role (Araujo et al 2017). The extent of this role is unlikely to be determined with any accuracy, but the likelihood that human beings played a part in such extinctions is supported by substantial evidence from across the world showing the decimation of indigenous species with the arrival of humans on previously uninhabited islands (de Nascimento et al 2020;Diamond 1989;Matthews et al 2020).…”
Section: Are Values Irrelevant To Environmental Impact?mentioning
confidence: 99%